Tantangan Bioetika dalam Penentuan Kelayakan Bekerja: Antara Otonomi dan Risiko Okupasi: Bioethical Challenges in Determining Work Eligibility: Between Autonomy and Occupational Risk - Rusli, Noer Triyanto (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
Fitness-for-work assessment is one of the core responsibilities in occupational medicine, particularly when dealing with workers experiencing health problems. This process requires not only accurate clinical judgment but also involves complex bioethical dimensions. This article aims to analyze the bioethical challenges faced by occupational physicians in determining fitness for work, with emphasis on the principles of autonomy, beneficence, non-maleficence, justice, and conflicts of interest. This study employs a qualitative approach through a systematic literature review and case reflections, complemented by semi-structured interviews with fifteen occupational health practitioners and human resource managers from the logistics, mining, and manufacturing sectors in Indonesia, conducted between January and May 2025. Data were analyzed thematically using a clinical bioethics framework. The findings reveal that medical decisions in this context often conflict with socio-economic pressures, productivity demands, and the limitations of Indonesia’s labor system. Power imbalances between employers and workers, low health literacy, and weak legal protection for medical professionals further exacerbate ethical dilemmas. Therefore, a multidisciplinary and systemic approach is needed—one that integrates ethical values into labor policy, occupational health training, and organizational governance. Fitness-for-work assessments should not merely serve as administrative procedures but must uphold justice, protect workers’ dignity, and reinforce the integrity of the medical profession.